2018
DOI: 10.1016/j.rser.2017.09.113
|View full text |Cite
|
Sign up to set email alerts
|

Processing thermogravimetric analysis data for isoconversional kinetic analysis of lignocellulosic biomass pyrolysis: Case study of corn stalk

Abstract: Modelling of lignocellulosic biomass pyrolysis processes can be used to determine their key operating and design parameters. This requires significant amount of information about pyrolysis kinetic parameters, in particular the activation energy. Thermogravimetric analysis (TGA) is the most commonly used tool to obtain experimental kinetic data, and isoconversional kinetic analysis is the most effective way for processing TGA data to calculate effective activation energies for lignocellulosic biomass pyrolysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
147
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 308 publications
(154 citation statements)
references
References 91 publications
6
147
0
1
Order By: Relevance
“…TGAs are widely applied in kinetic studies because of their ability to measure sample weight loss and temperature measurement with respect to reaction time (Bach & Chen, 2017;Cai et al, 2018;Murillo, Biernacki, Northrup, & Mohammad, 2017;Wang et al, 2016). Thermogravimetric data and differential thermogravimetric data (DTG) facilitate identification of various stages of biomass pyrolysis and temperature ranges for the decomposition of biomass components, respectively (Dollimore, Evans, Lee, & Wilburn, 1992).…”
Section: Thermogravimetric Analyzersmentioning
confidence: 99%
See 2 more Smart Citations
“…TGAs are widely applied in kinetic studies because of their ability to measure sample weight loss and temperature measurement with respect to reaction time (Bach & Chen, 2017;Cai et al, 2018;Murillo, Biernacki, Northrup, & Mohammad, 2017;Wang et al, 2016). Thermogravimetric data and differential thermogravimetric data (DTG) facilitate identification of various stages of biomass pyrolysis and temperature ranges for the decomposition of biomass components, respectively (Dollimore, Evans, Lee, & Wilburn, 1992).…”
Section: Thermogravimetric Analyzersmentioning
confidence: 99%
“…Through TGA studies the decomposition of cellulose, hemicellulose, and lignin was found to occur in reasonably distinct temperature ranges, 300-400, 200-380 and above 400 C, respectively (Yang, Yan, Chen, Lee, & Zheng, 2007). This topic has been extensively reviewed by Bach and Chen (2017), Cai et al (2018), Murillo et al (2017), and Wang et al (2016). For over several decades, TGA-based studies are being performed to gather global kinetics of biomass and its components but no intrinsic kinetics can be elucidated.…”
Section: Thermogravimetric Analyzersmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignocellulosic biomass is a resource for renewable electricity, thermal energy, biofuels, and chemicals. 1 According to the International Coffee Organization, coffee is widely produced worldwide, and it is considered as the second largest traded commodity in the world. Coffee plants are cultivated in 98% of the world countries.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling of lignocellulosic biomass pyrolysis processes can be used to determine their key operating and design parameters. 1 To estimate the kinetic parameters of pyrolysis process, thermogravimetric analyses can be used. This technique enables the description and interpretation of the phenomena of biomass decomposition.…”
Section: Introductionmentioning
confidence: 99%